2019
DOI: 10.1016/j.aott.2019.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous fixation of Lisfranc joint injuries: A systematic review of the literature

Abstract: ObjectiveThe aim of this systematic review was to present the outcome of Lisfranc joint injuries treated with closed reduction and screw percutaneous fixation.MethodsWe searched in Pubmed and Google Scholar Databases for articles regarding screw percutaneous fixation of Lisfranc injuries. Seven studies in total were found to be compatible to our search, according to PRISMA guidelines. Four of those met the criteria of the review and they were included in the meta-analysis. A total number of 106 patients were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In a systematic review of 106 patients, Stavrakakis et al demonstrated good functional outcomes for patients treated with closed reduction and percutaneous fixation. 61 The main benefit of percutaneous fixation like other minimally invasive operative techniques is a reduction in soft tissue damage and minimization in morbidity from traditional open surgeries. 67 However, when compared to closed reduction, open reduction better achieves anatomic restoration.…”
Section: Outcomes and Complicationsmentioning
confidence: 99%
“…In a systematic review of 106 patients, Stavrakakis et al demonstrated good functional outcomes for patients treated with closed reduction and percutaneous fixation. 61 The main benefit of percutaneous fixation like other minimally invasive operative techniques is a reduction in soft tissue damage and minimization in morbidity from traditional open surgeries. 67 However, when compared to closed reduction, open reduction better achieves anatomic restoration.…”
Section: Outcomes and Complicationsmentioning
confidence: 99%
“…Only 1 systematic review on percutaneous fixation has been performed by Stavrakakis et al, including just 4 studies, which concluded that percutaneous fixation was simple, safe, and with a low operative morbidity 55 . However, as with any periarticular injury, a positive outcome was reliant on anatomical reduction, and some authors consider an open reduction mandatory for all subtle Lisfranc injuries to prevent missing concomitant joint injury, which if left untreated may lead to post-traumatic arthritis 21 .…”
Section: Percutaneous Fixationmentioning
confidence: 99%
“…Another controversial point is the infection and dehiscence rates related to the surgical wound needed for reduction which reach up to 12.5% in a systematic review published in 2019 5,6…”
Section: Historical Perspectivementioning
confidence: 99%
“…4 Another controversial point is the infection and dehiscence rates related to the surgical wound needed for reduction which reach up to 12.5% in a systematic review published in 2019. 5,6 With the emergence of minimally invasive surgery in the trauma setting, and bearing in mind that the percentages of complications and sequelae despite the good results in reduction quality are still important, we began to use minimally invasive surgery reduction and fixation in the treatment of Lisfranc complex injuries.…”
Section: Historical Perspectivementioning
confidence: 99%